¿La modalidad relegada o la función prototipica recalcada? Acerca de la oposición pretérito perfecto/pretérito indefinido/pretérito imperfecto de indicativo en los métodos de ELE - Baran, Marek (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The subject of the present article is the place which is attributed to the modality in pedagogical approaches of the system of past tenses in Spanish. This analysis indicates that in ELE handbooks, very often, the comparison between Pretérito Perfecto and Pretérito Indefinido is based on time criteria without taking into consideration the pragmatics, such as: the relation established by the speaker between himself and the statement he makes. Besides, the idea of temporality, suggested there, has little to do with linguistic temporality. Which in turn leads to the falseness on the level of discourse and language categories.
The relegated modality or the prototypical function emphasised? Pretérito perfecto, pretérito indefinido, pretérito imperfecto de indicativo in the ELE teaching